Geolocalised social networks for the characterisation and assesment of public space: The squares of the historic centre of the city of Seville - Becerra-Fernández, Daniel; Díaz-Cuevas, Pilar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper analyses the squares in the historic centre of Seville, the diversity and intensity of use that they currently support. For this purpose, spatial data on the squares, obtained from “OpenStreetMap”, their origin, historical development, etc., have been compiled. Geographic Information Systems are used to combine the above information with data from the “InstaSights” application, related to nightlife, hospitality spaces, shopping areas and sightseen areas. It is found that the public squares in the central and southern neighbourhoods of the historic centre of Seville present the greatest diversity and intensity of use.